A cárie dentária no curso da vida: análise longitudinal baseada na mobilidade educacional e trajetória de renda - Filgueira, Adriano de Aguiar (2025)
Dental caries is considered a public health problem and its main consequence is edentulism, which mainly affects adults and the elderly. Understanding how events throughout life affect the health-disease process is important in building strategies that improve the population's quality of life. The objective of this work was to investigate tooth decay in adults based on the intergenerational educational trajectory and socioeconomic trajectory throughout life. For this, we used data from an oral health cohort carried out in the municipality of Sobral, which has four waves: 2000, 2006, 2012 and 2022, in which 224 people participated at all times. When using data only from 2000 and 2022, the total sample was 275, since 51 subjects did not participate in at least one wave. For data collection, a structured questionnaire was applied and an oral examination was carried out following the WHO methodology for epidemiological examinations. For data collection, a structured questionnaire was applied and an oral examination was carried out following the WHO methodology for epidemiological examinations. For this thesis, two chapters were constructed. The first is intergenerational educational mobility, in which a trajectory was constructed based on parental education in 2000 and the adult's educational level in 2022. The outcome variable consisted of the number of decayed teeth not treated in the last wave. The sample consisted of 275 adults aged 27 to 31 years. The results showed that adults who did not reach high school and lived with illiterate heads of families had a higher average number of decayed teeth (x̅ = 5.20; SD = 1.31) when compared to those who managed to complete high school (x̅ = 2.02; SD = 1.72) even when adjusted for per capita income, gender and use of toothbrush, toothpaste and dental floss (p <0.001). Participants who lived with heads of families who had completed primary education and had completed secondary education (x̅ = 2.29; SD = 2.59) or higher education (x̅ = 1.35; SD = 1.86) had lower average number of decayed teeth when compared to those who were unable to reach secondary level (x̅ = 4.87; SD = 5.55; p =0.01) or higher education (x̅ = 3.15; SD = 3.15; p = 0.02). The second chapter used tooth loss as an outcome according to socioeconomic trajectory, which was based on the number of episodes of poverty throughout life. 224 adults participated in this study. When compared with the group that always presented the best tertile of per capita income and adjusted for sex, race, smoking, level of education of the head of the family, Significant Index Caries and trajectory of use of dental services, those who experienced 1 or 2 episodes of poverty had a higher risk of losing teeth [RR = 1.48 (1.04-2.11); p = 0.029]. The risk was even greater among those with 3 or 4 episodes of poverty [RR = 1.68 (1.10-2.57); p = 0.015). It can be concluded that worse life trajectories and intergenerational educational mobility are risk factors in the development of tooth decay and tooth loss in adult life.